DEPRESI DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PADA PENDERITA THALASSEMIA BETA MAYOR - , Komang Ayu R Purnamaningsih ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Thalassemia is one of hereditary hemolytic anemia. Indonesia is located on the thalassemia belt region with high prevalence of thalassemia. Children with chronic illness including thalassemia have been proven to be a substantial risk for psychosocial problems such as depression. Objective: To assess frequency of depression and identify factors associated with depression in beta thalassemia major patients. Methods: A cross-sectional study was conducted on July-August 2012. We enrolled: 7-12 years old beta thalassemia major patients